4-Phenethylthio-2-phenylpyrazolo[1,5-a][1,3,5]triazin-7(6H)-one - Smolnikov, S.; Gorgopina, E.; Lezhnyova, V.; Ong, G.; Chui, W.; Dolzhenko, Anton (2017)
© 2017 by the authors. Licensee MDPI, Basel, Switzerland. Exploring the pharmacologically important pyrazolo[1,5-a][1,3,5] triazin-7(6H)-one scaffold for the construction of new bioactive compounds, we developed a synthesis of 4-phenethylthio-2- phenylpyrazolo[1,5-a][1,3,5] triazin-7(6H)-one (4) via S-alkylation of 2-phenyl-4-thioxopyrazolo [1,5-a][1,3,5] triazine-7(6H)-one (3), prepared by the double ring closure of pyrazole and triazine rings upon the treatment of 1-cyanoacetyl-4-benzoylthiosemicarbazide (2) with alkali. The antiproliferative activity of 4 against human lung cancer (A549) and human breast cancer (MDA-MB231) cell lines was investigated. Compound 4 was found to be more active against lung cancer cells t han breast cancer cells.